A Needs Analysis of Karate Kumite With Recommendations for Performance Testing and Training. Issue 3 (June 2019) - Chaabene, Helmi; Negra, Yassine; Capranica, Laura; Prieske, Olaf; Granacher, Urs
Abstract : ABSTRACT: AN EFFECTIVE TRAINING PROGRAM NEEDS TO BE CUSTOMIZED TO THE SPECIFIC DEMANDS OF THE RESPECTIVE SPORT. THEREFORE, IT IS IMPORTANT TO CONDUCT A NEEDS ANALYSIS TO GAIN INFORMATION ON THE UNIQUE CHARACTERISTICS OF THE SPORT. THE OBJECTIVES OF THIS REVIEW WERE (A) TO CONDUCT A SYSTEMATIC NEEDS ANALYSIS OF KARATE KUMITE AND (B) TO PROVIDE PRACTICAL RECOMMENDATIONS FOR SPORT-SPECIFIC PERFORMANCE TESTING AND TRAINING OF KARATE KUMITE ATHLETES. FOR A VIDEO ABSTRACT OF THIS ARTICLE SEE SUPPLEMENTAL DIGITAL CONTENT 1, HTTP://LINKS.LWW.COM/SCJ/A248. Abstract : Supplemental Digital Content is Available in the Text.